MEMPERTEGAS IDE KESETARAAN GENDER DALAM SISTEM KEWARISAN BILATERAL : Sistem Waris Bilateral Pasca Hazairin - Aniroh, Reni Nur (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
This article examines the development of the idea of bilateral inheritance coined by Hazairin which insists on the existence of men and women heirs. Hazairin argued that the nature of Islamic law of inheritance is bilateral. Hazairin’s concept of bilateral inheritance has been echoed by some Muslim scholars in Indonesia. This article tries to explain the development of bilateral inheritance in Indonesia by elucidating some concepts of Islamic inheritance law proposed by some Muslim scholars in Indonesia. Munawir Sadzali with his Reaktualisasi Ajaran Islam has tried to make the concept down to the earth by formulating quantitative equality between men and women shares. Harahap has come with the idea of one portion as the minimum share and the double as the maximum share of the estate of the heirs. Sarmadi proposed joint property and obligatory will as a tool of controling equality among the heirs. From the perspective of the history of law, the concept of bilateral inheritance has developed in line with the development of Indonesian context. The concept did not only consider the textual meaning of the text and Indonesian context, but also the development of family structure among the society, gender equality, and equality as the main purpose of Islamic inheritance law mentioned in the Qur’anic verses.Artikel ini membahas tentang perkembangan konsep waris bilateral yang digagas oleh Hazairin yang fokus pada keberadaan ahli waris laki-laki dan ahli waris perempuan. Hazairin berpendapat sistem waris bilateral ini menjadi watak dasar hukum waris Islam. Pasca Hazairin, konsep waris bilateral ini telah diusung kembali oleh beberapa sarjana Muslim Indonesia. Tulisan ini menjelaskan tentang perkembangan sistem waris bilateral di Indonesia dengan menelisik beberapa pemikiran hukum waris Islam yang disuarakan oleh beberapa sarjana Muslim Indonesia. Munawir Sadzali dengan ide tentang Reaktualisasi Ajaran Islam menawarkan adanya persamaan secara kuantitatif antara ahli waris laki-laki dan perempuan. Yahya Harahap menawarkan konsep satu bagian sebagai batas minimal dan dua bagian sebagai batas maksimal yang dapat diterima oleh ahli waris. Sedangkan Sarmadi menawarkan konsep harta bersama dan wasiat wajibah sebagai bagian alat kontrol pembagian waris di Indonesia. Dari perspektif sejarah hukum, ide tentang hukum waris bilateral telah berkembang sesuai dengan konteks Indonesia. Konsep waris bilateral tidak hanya mempertimbangkan makna ayat dan konteks Indonesia, tetapi juga perkembangan struktur dan hubungan kekerabatan, keadilan gender, dan keadilan sebagai tujuan utama kewarisan hukum Islam seperti yang disebutkan dalam ayat-ayat waris.